A SNAP25 promoter variant is associated with early-onset bipolar disorder and a high expression level in brain - Etain, Bruno (Nature Publishing Group Specialist Journals, 2010)
Bipolar disorder (BD) is one of the most common and persistent psychiatric disorders. Early-onset BD has been shown to be the most severe and familial form. We recently carried out a whole-genome linkage analysis on sib-pairs affected by early-onset BD and showed that the 20p12 region was more frequently shared in our families than expected by chance. The synaptosomal associated protein SNAP25 is a presynaptic plasma membrane protein essential for the triggering of vesicular fusion and neurotransmitter release, and for which abnormal protein levels have been reported in postmortem studies of bipolar patients. We hypothesised that variations in the gene encoding SNAP25, located on chromosome 20p12, might influence the susceptibility to early-onset BD. We screened SNAP25 for mutations and performed a case-control association study in 197 patients with early-onset BD, 202 patients with late-onset BD and 136 unaffected subjects. In addition, we analysed the expression level of the two SNAP25 isoforms in 60 brains. We showed that one variant, located in the promoter region, was associated with early-onset BD but not with the late-onset subgroup. In addition, individuals homozygous for this variant showed a significant higher SNAP25b expression level in prefrontal cortex. These results show that variations in SNAP25, associated with an increased gene expression level in prefrontal cortex, might predispose to early-onset BD. Further analyses of this gene, as well as analysis of genes encoding for the SNAP25 protein partners, are required to understand the impact of such molecular mechanisms in BD.